PEMETAAN AIR TANAH DI KABUPATEN JENEPONTO DENGAN METODE GEOLISTRIK - As?ari, As?ari (IAIN Batusangkar, 2011)
Data prossesing of groundwater estimate research at Kabupaten Jeneponto, Provinsi Sulawesi Selatan had been done. The research use geoelectric method and Schlumberger configuration. The result of 2-D inversion IP2WIN software show that this method can use for groundwater estimation. We had information of area where there had groundwater potention. Research area divided to 6 path, we know locate and depth information of groundwater from each path, on path 1: Desa Bontorappo and Desa Arungkeke have lower groundwater at 5-15 meter depth and deep groundwater at 45-50 meter depht. Path 2: Desa Balangloe Tarowang and Desa Arungkeke have lower groundwater at 1-15 meter depth and deep groundwater at 20-55 meter depht. Path 3: Kelurahan Benteng have groundwater at 0-100 meter depht. Path 4: Desa Bangkala have groundwater at 30-50 meter depht. Path 5: Desa Torokassi have groundwater at 20-55 meter depht.Key words: groundwater, geoelectric method, Schlumberger configuration